Static and dynamic price effects motivated by innovation and imitation: Novel insights using the Barone's curve - Valentyna Antonenko; Leonid Katranzhy; Kostiantyn Moiseienko; Svitlana Yudina; Olha Brezhnyeva-Yermolenko; Svitlana Hanziuk; Aiste Galnaityte; Virginia Namiotko (Contemporary Economics, 2020)
Luigi Barone's famous curve offers an excellent framework for the study of the microeconomic and macroeconomic implications of innovation and imitation. However, neither Barone nor his epig- ones have been able to sufficiently "exploit" his contribution to date. Complementing his analysis of supply (covering unit costs and marginal costs of production) to the forces of aggregate demand provided by the macroeconomic aggregate demand-aggregate supply model (AS-AD) analysis would be required in order to identify the determinants of the equilibrium price level in the econ- omy. Moreover, a dynamic interpretation (provided by an inhomogeneous difference equation of the second order) of Barone's key economic growth factors (innovation and imitation) makes it easier to identify the cyclical properties of the macroeconomic price changes. These cyclical price movements have proven to be empirically relevant in the case of Germany (2000-2017), while patent record (as an indicator for the occurrence of innovation) appears to follow a random walk (Germany, 2000-2017).
Keywords: B31; B22; E32; O31; O11; O47; 330; Innovation; imitation; Barone's Curve; static and dynamic modeling of macroeconomic price (change) formation